Development of flax/basalt/PA11 bio-composites: optimal formulation and modelling of the quasi-static behaviour - Guerfala, Wassim; Rozycki, Patrick; Binetruy, Christophe (Frontiers in Materials, 2023)
Environmental impact is becoming increasingly important in the automotive industry, with car manufacturers looking to reduce CO2 emissions through cleaner engines and structural weight reduction. Composite materials offer an excellent alternative to standard steels with significant weight reduction and the ability to produce functional parts (Rangappa et al., Polymer Composites, 2022,43, 645–691), (Jeyaguru et al., Polymer Composites, 2022, 43, 3902–3914), (Sanjay et al., Journal of Cleaner Production, 2018, 172, 566–581). The main objective of this study is to investigate the potential of a new and unique hybrid bio-composite material combining flax and basalt fibers and PA11 polymer. This material design is studied with the idea of reducing the moisture sensitivity, variabilities, and uncertainties of vegetal fibers by the presence of basalt fibers. The first step consists of developing a new hybrid composite material and studying its quasi-static mechanical behaviour when subjected to different humidity levels. Then, a multi-scale non-linear homogenization approach is proposed to support the interpretation of the characterization test results. The experimental results show the benefits of the hybridization. In fact, the hybrid composite is 20% stiffer than the flax/PA11 composite, 8% lighter than the basalt/PA11 composite and has a reduced dispersion of its mechanical properties, 52% lower than the flax/ PA11 composite. Considering the promising properties of the hybrid composite, we have investigated the possibility of developing the front hood of a sports car using this material. The first results highlight a potential mass gain of 18% at iso-performance with the original front hood. The following steps will be devoted to the numerical and experimental validation.